PENGARUH CITRA PARTAI PENDUKUNG, IKLAN POLITIK DAN KELOMPOK REFERENSI TERHADAP MINAT MEMILIH CALON KEPALA DAERAH DALAM PEMILIHAN KEPALA DAERAH KABUPATEN PELALAWAN - Khalil, Tengku Fardhian (Jurnal Tepak Manajemen Bisnis, 2014)
The success of the election is affected by the level of political participation of the people who wereinvolved or get involved in every stage of the election process, including the implementation of PelalawanRegencyâs Election in 2011. Some of the factors variables thought to influence the political participation of thepeople in the General Election Pelalawan Regency is supporting partyâs image (X1), political advertising (X2),the reference group (X3) and interests choosing (X4). The purpose of this study was to analyze the effect ofsupporting partyâs image, political advertising and the reference group against interests choosing in PelalawanRegencyâs General Election, so that unknown variable factors which are the most dominant influence on theinterest choose. The study used descriptive quantitative approach, where the population is citizens who are inthe permanent voters list (DPT) in two villages/urban, is Pangkalan Kerinci urban and Teluk Meranti villagewith number of respondents as many as 150 people. The results show the influence of the supporting partyâsimage probability the interest of selecting significance level is 5% mean 0.368, political advertising at 0.060and influence of references group interest choosing at 0.163. This suggests that the effect of supporting partyâsimage to select is the dominant interest with a probability of 0.368.